Публицистика Владимира Короленко - Bortnowski, Antoni (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
Journalism takes a very important place in the works of Vladimir Korolenko. The writer witnessed historic changes in Russia of the late 19th — early 20th century and in his many works included a great number of valuable comments and insightful analysis of the processes taking place on the territory of the decaying Russian Empire. The last years of the writer's life coincided with a period of formation of the Soviet authority, which Korolenko did not accept. This fact was often overlooked or ignored in the Soviet critical works on the writer and only after the collapse of the USSR it was possible to conduct an overall analysis of Korolenko’s rich heritage. Many of his articles containing insights into the Russian reality can be applied to modern times.